Birodalom gyarmat nélkül - Gerő, András (Közép-Európai Közlemények, 2013)
The Austro–Hungarian Monarchy was the only European great power which did not have colonies. Formally there was a base for the colonisation: the Empire at the beginning of the XX. century had the sixth biggest fleet in Europe and serious surplus in the labour force which finally left the Monarchy and went first of all to United States. The colonisation in the self-identity of Austro–Hungarian Empire was a missing element –it was not the part of the so-called „raison d’etat”. In other European states the colonisation gave a mission function for the given nation; it created a cohesion for the given state. In Austro–Hungarian Empire the missing colonisation created the idea of inner colonisation. The Hungarians was complaining on Austrian colonisation and practically each nation complained on the repression by other nation.